Pinoy capital the Filipino nation in Daly City - Vergara, Benito M. Jr. 1970- (Philadelphia Temple University Press, 2009)
Home to 33,000 Filipino American residents, Daly City, California, located just outside of San Francisco, has been dubbed "the Pinoy Capital of the United States". This title studies the lives of Daly City residents, showing how Daly City has become a magnet for the growing Filipino American community.
A repeated turning -- Little Manila -- Looking forward : narratives of obligation -- Spreading the news : newspapers and transnational belonging -- Looking back : indifference, responsibility, and the anti-Marcos movement in the United States -- Betrayal and belonging -- Citizenship and nostalgia -- Pinoy capital.
Includes bibliographical references (pages 207-214) and index.
Keywords: Filipino Americans -- Social conditions. -- California -- Daly City; Filipino Americans -- Ethnic identity. -- California -- Daly City; Immigrants -- Social conditions. -- California -- Daly City; Community life -- California -- Daly City; Transnationalism